Our Family Functions: Functions of Traditional Weddings for Modern Brides and Postmodern Families - Barnes, Medora W. (Qualitative Sociology Review, 2014)
In many ways the continued popularity of traditional weddings in the United States may seem surprising in light of the increased rates of divorce, cohabitation, and non-marital child-bearing in the latter half of the twentieth century, which have accompanied the rise of what has come to be called the “postmodern” family. This research draws upon in-depth interviews with twenty white, middle class women who recently had traditional weddings and explores the connections between the postmodern family context and the desirability of traditional weddings. Specifically, it examines how traditional functions of formal weddings are still relevant within contemporary society. Findings indicate that the traditional functions of weddings operate differently in the current family context, but are important aspects of the appeal of formal weddings for modern brides. Large, formal weddings encourage extended family bonding, which may be more important now than in past decades due to the high rates of divorce and remarriage. New “invented traditions” are sometimes being included in weddings to allow for the participation of the wider range of family members that exists in post-modern families. Furthermore, having a large, traditional wedding may serve to decrease anxiety about marriage through providing a predictable entry into marriage and a testing ground for the couple’s marital work ethic.